Neurotoxicity of Nanomaterials: An Up-to-Date Overview - Teleanu, Daniel Mihai (Nanomaterials (Basel), 2019)
The field of nanotechnology, through which nanomaterials are designed, characterized, produced, and applied, is rapidly emerging in various fields, including energy, electronics, food and agriculture, environmental science, cosmetics, and medicine. The most common biomedical applications of nanomaterials involve drug delivery, bioimaging, and gene and cancer therapy. Since they possess unique properties which are different than bulk materials, toxic effects and long-term impacts on organisms are not completely known. Therefore, the purpose of this review is to emphasize the main neurotoxic effects induced by nanoparticles, liposomes, dendrimers, carbon nanotubes, and quantum dots, as well as the key neurotoxicology assays to evaluate them.